Bioprinting Methods for Fabricating In Vitro Tubular Blood Vessel Models - Seon-Jin Kim; Min-Gyun Kim; Jangho Kim; Jessie S. Jeon; Jinsoo Park; Hee-Gyeong Yi (Cyborg and Bionic Systems, 2023)
Dysfunctional blood vessels are implicated in various diseases, including cardiovascular diseases, neurodegenerative diseases, and cancer. Several studies have attempted to prevent and treat vascular diseases and understand interactions between these diseases and blood vessels across different organs and tissues. Initial studies were conducted using 2-dimensional (2D) in vitro and animal models. However, these models have difficulties in mimicking the 3D microenvironment in human, simulating kinetics related to cell activities, and replicating human pathophysiology; in addition, 3D models involve remarkably high costs. Thus, in vitro bioengineered models (BMs) have recently gained attention. BMs created through biofabrication based on tissue engineering and regenerative medicine are breakthrough models that can overcome limitations of 2D and animal models. They can also simulate the natural microenvironment in a patient- and target-specific manner. In this review, we will introduce 3D bioprinting methods for fabricating bioengineered blood vessel models, which can serve as the basis for treating and preventing various vascular diseases. Additionally, we will describe possible advancements from tubular to vascular models. Last, we will discuss specific applications, limitations, and future perspectives of fabricated BMs.